The Oxford handbook of the economy of Cameroon - Monga, Célestin (Oxford handbooks, 2022)
This work provides a critical assessment of the history, patterns, and strategies of economic development in Cameroon, and outlines new approaches to economic enquiry for prosperity and social change.